ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH YANG TERDAFTAR DI BANK INDONESIA - Liora, Elsa Fibeany; Taufik, Taufeni; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to compare the financial performance of Islamic bankingwith conventional banking in the period 2010-2012 by using financial ratios. Financial ratios used consisted of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA), Biaya Operasional terhadap Pendapatan Operasional (BOPO), and Loan to Deposit Ratio (LDR).The population in this research is 134 companies Islamic banking andconventional banking which are listed Bank of Indonesia during the period of 2010-2012 while the amount of the research samples are 20 banks, is 10 conventional banks and 10 islamic banks. This study using hypothesis testing the "Independent Sample t-Test" to see the difference in the financial performance of Islamic banking with conventional banking as a whole.The results showed that Non Performing Loan (NPL), Return On Assets(ROA), Biaya Operasional terhadap Pendapatan Operasional (BOPO) do not differ significantly between Islamic banks with the conventional banks, Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) that showed significant differences between Islamic banking and conventional banking. The signifiant value of the Capital Adequacy Ratio (CAR) 0.005, Loan to Deposit Ratio (LDR) 0.000, Non Performing Loan (NPL) 0.598, Return On Assets (ROA) 0.845, and Biaya Operasional terhadap Pendapatan Operasional (BOPO) 0.259.Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA), Biaya Operasional terhadap Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR)